Pengaruh Kepemimpinan, Kedisiplinan Dan Komunikasi Terhadap Kinerja Melalui Motivasi Pada Tutor Universitas Terbuka (Studi Pada Kelompok Belajar Wonosobo II UPBJJ Yogyakarta Universitas Terbuka) - Harsono, Slamet (STIE AUB Surakarta)
The purpose of this research is to know and examine the influence of Leadership, Discipline and Communication on Performance Through Motivation in Open University Tutor (Study on Wonosobo II Learning Group UPBJJ Yogyakarta Open University). Data collection techniques using documentation, observation, and questionnaire, the sampling method was census method. Analysis using path analysis (path analysis). The result of t test shows that Leadership has an insignificant effect on the motivation of open university tutor. Discipline has no significant effect on the motivation of open university tutors. Communication has no significant effect on the motivation of open university tutors. Leadership has a significant effect on the performance of open university tutors. Discipline has no significant effect on the performance of open university tutors. Communication has a significant effect on the performance of open university tutors. Motivation has no significant effect on the performance of open university tutors.F test results show that leadership, discipline, communication and motivation together have a significant effect on the performance of open university tutors. The result of total coefficient determination test 41,8%. This means that the performance of university tutor tutors is open, explained by Leadership, discipline, communication and motivation variables as intervening variable of 41.8%. And the remaining 58.2% described other variables outside the research model, for example, organizational culture and commitment, the work environment not included in the model. The result of path analysis shows that communication has significant effect to performance, is the most dominant path.Keywords: Leadership, Discipline, Communication, Motivation and Performance